Il ladro di Salvagno: Una congettura per la tenzone con Forese (Carte Romanze, 2020)
The paper analyses the romance sources about a character called Salvain, Selvain or Servein (italian Salvagno), and proposes a conjecture for verse 14 of Dante’s sonnet Ben ti faranno il nodo Salamone.